Construction of a social accounting matrix for Kenya 2009 - Omolo, Miriam W. O. (International Food Policy Research Institute, 2014)
This paper sought to construct a social accounting matrix for Kenya 2009 given that the most recent SAM dates back to 2003. The objective of this exercise was to construct a micro SAM incorporating accounts of individual activities, primary factors, and economic institutions and to balance the SAM using cross entropy method. The SAM 2009 provides a new opportunity for modelers to use most recent Kenyan SAM to undertake economy wide analysis.